Cost-Benefit Analysis in World Bank Projects - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This report has been prepared in the context of a major global effort in the past eight years to better measure results in development assistance. The agenda for this effort was articulated and refined in a series of international conferences, beginning with the international conference on financing for development in Monterrey in 2002 and continuing through the Accra agenda for action in 2008. Cost-benefit analysis entails measuring results, valuing results, and comparing results with costs, and hence is highly relevant to the results agenda. Cost-benefit analysis can provide a comprehensive picture of the net impact of projects and help direct funds to where their development effectiveness is highest. This study draws two broad conclusions. First, the bank needs to revisit its policy for cost-benefit analysis in a way that recognizes the legitimate difficulties in quantifying benefits while preserving a high degree of rigor in justifying projects. Second, the bank needs to ensure that cost-benefit analysis is done with quality, rigor, and objectivity: poor data and analysis misinform, and do not improve, results. Reforms are required to project-appraisal procedures to ensure objectivity, improve both the analysis and the use of evidence at appraisal, and ensure effective use of cost benefit analysis in decision making.